Comparison of second molar protraction using different timing for piezocision application: A randomized clinical trial - Elham S. ABU ALHAIJA; Marwan M. AL-AREQI; Emad F. AL MAAITAH (Dental Press Editora, 2022)
ABSTRACT Objective: To compare second molar protraction between early, late and no piezocision groups. Material and Methods: Forty subjects with bilaterally extracted mandibular first molars were selected to participate in the study. Subjects were subdivided into two groups: piezocision and no piezocision. The piezocision group was further subdivided into two subgroups: early piezocision (piezocision performed immediately before second molar protraction) and late piezocision (piezocision performed three months after starting molar protraction). In the no piezocision group, molar protraction was done without surgery. The intervention (piezocision group and timing of piezocision/side within group) was randomly allocated using the permuted random block size of 2, with 1:1 allocation ratio. The amount of second molar protraction, duration of space closure and anterior anchorage loss were measured. A repeated measures analysis of variance was conducted to define the differences between the measured variables at the different time intervals. Differences between groups were assessed using ANOVA test. Results: No difference was detected between early and late piezocision groups in the amount of molar protraction at the end of space closure. Duration of complete space closure was 9 and 10 months in the piezocision and no piezocision groups. Anchorage loss was similar between the three studied groups. Conclusions: Early and late piezocision have similar effect and both increased the amount of second molar protraction temporarily in the first 2-3 months after surgery. Duration of mandibular first molar space closure was reduced by one month when piezocision was applied. Anchorage loss was similar in the three groups.